PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI ”DUNIA RAHASIA TUMBUHAN” BERBASIS AI UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN TLOGOSARI KULON 04 - Prita Iswa Salma; Husni Wakhyudin; Arfilia Wijayanti (STKIP Subang, 2025)
This study is motivated by the low level of students’ understanding of the plant material in the IPAS subject for Grade IV students at SDN Tlogosari Kulon 04. This is due to the lack of engaging learning media, which leads to students being less active during the learning process. Therefore, it is necessary to develop instructional media that can help students comprehend the material and actively participate in learning. One proposed solution is the use of an AI-based animated video learning media titled